On gender stereotypes of the Scandinavian society in the Viking Age (Theatrum historiae, 2009)
This article, based on Scandinavian narrative sources (tha sagas), skaldic and eddic poetry as well as medieval law-codes, presents a particular view of the Scandinavian gender history during the Viking Age. Scandinavian historiographies have paid attention to gender studies for several last decades, specially to long time neglected women ́s history. However, this contribution focuses on the dominant male element of the Viking society and seeks answers to questions like „How the Viking Age society defines manhood and man's characteristic behaviour?“, „What kind of act or social position had been abominated by Norse society?“ or „Had the social roles been determined by biological bindings?“. The main aim of this study is denial of typical social stereotypes of the Viking Age society as man-protector and provider of his family and woman „Lady of the keys“ (i.e. housewife) which authoress conciders only as literary topoi.